2020
DOI: 10.1007/s00595-020-01981-0
|View full text |Cite
|
Sign up to set email alerts
|

Are graduating residents sufficiently competent? Results of a national gap analysis survey of program directors and graduating residents in Japan

Abstract: Purpose: To determine the self-assessed competency of graduating residents (GRs) in Japan upon completion of their residency and to determine the gap between their competency and the competency expected by their program directors (PDs). Method:A list of 31 essential surgical procedures was compiled according to the consensus of surgical educators from around the country. A survey with this list was sent to all 909 GRs and their 611 PDs in 2016. The GRs rated their competency to perform these procedures and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
1
2
0
1
Order By: Relevance
“…Several previous studies involving general surgery revealed that trainees did not achieve sufficient surgical competencies after their residency periods. [1][2][3] In urology, similar trends have also been reported, for example, in the United States, a survey of US urology residents/recent graduates and program directors revealed a lack of confidence in performing unsupervised advanced laparoscopic and robotic surgeries in most residents. 4 A national survey in Italy also observed that more than 70% of residents had never performed a robotic procedure during training.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Several previous studies involving general surgery revealed that trainees did not achieve sufficient surgical competencies after their residency periods. [1][2][3] In urology, similar trends have also been reported, for example, in the United States, a survey of US urology residents/recent graduates and program directors revealed a lack of confidence in performing unsupervised advanced laparoscopic and robotic surgeries in most residents. 4 A national survey in Italy also observed that more than 70% of residents had never performed a robotic procedure during training.…”
Section: Introductionsupporting
confidence: 55%
“…However, due to working‐hour restrictions and medical safety, young trainees now face difficulty in accumulating sufficient surgical caseloads during training periods. Several previous studies involving general surgery revealed that trainees did not achieve sufficient surgical competencies after their residency periods 1–3 . In urology, similar trends have also been reported, for example, in the United States, a survey of US urology residents/recent graduates and program directors revealed a lack of confidence in performing unsupervised advanced laparoscopic and robotic surgeries in most residents 4 .…”
Section: Introductionmentioning
confidence: 55%
“…Para tal fin se utilizan los instrumentos de evaluación formativa (entrevistas documentadas, informes), informes de rotaciones y el libro del residente. En el futuro es posible que lleguen a implementarse pruebas tipo ECOE, o valoraciones individuales como la aplicación de escalas como la de Zwisch para competencias técnicas o la NOTSS (Non-Technical Skills for Surgeons) y similares para competencias no técnicas (7,8). Toda la documentación acreditativa de las evaluaciones ha de quedar en el expediente del residente.…”
Section: Comité De Evaluaciónunclassified
“…The Halstedian apprenticeship training model in surgery has undergone significant revolution in recent decades 1. Evolving patient expectations regarding the role of surgical trainees in their care,2 an emphasis on theatre efficiency,3 increased demands on the surgical workforce4 and concerns regarding perceived operative competence and confidence of graduating trainees,5–7 have led to a re-evaluation of the training paradigm. The implementation of work-hour restrictions,8 9 and the requirement to train and retain a diverse workforce10 present opportunities to rethink the way in which surgeons are trained.…”
Section: Introductionmentioning
confidence: 99%